Marketization and social work with people with disabilities: ethical and theological reflections - Eurich, Johannes (Diaconia, 2010)
In this article, I argue that marketization has double effects: the concept of the customer benefits those individuals with disabilities who are able to manage daily affairs, often by the help of assistants. Their self-determination is enhanced so that participation in societal life can be more easily achieved. On the other side, marketization is not geared to consider the needs of the most handicapped people. They are often unable to meet the challenges that are involved by introducing the concept of the customer. Another ethical orientation is necessary in order to meet their special needs. One foundation for this orientation can be seen in the theological understanding of love which includes all human beings without any precondition. Although the argument followed a Christian perspective, loving one's neighbour can be embraced by secular persons as well. This orientation is needed in order to balance the negative effects of market forces on more severely disabled people.
Gesehen am 12.07.2016